Feasibility study of the implementation of health promoting processes in a secondary school and ways to capture its impact on adolescent lifestyle choices - C.A. Forbes; A.J. Williams; K. Wyatt (Public Health in Practice)
Objectives: Schools are environments that influence adolescent health choices; understanding schools as complex adaptive systems, we have developed a series of processes that are adaptive to the school context, to support schools to create the conditions for health promotion. The aim of this study was to determine the feasibility and acceptability of capturing the impact of implementing the health promoting school (HPS) process. Study design: feasibility study. Methods: A purposefully selected secondary school in England, with high Free School Meal (FSM) allocation, was recruited to implement the HPS processes, which includes an annual school audit. We developed a questionnaire, to capture lifestyle behaviours and school culture, completed before the audit and 9 months after. Descriptive analysis analysed the questionnaire responses to understand whether it captured similar responses to the audit. Post intervention interviews with staff and a focus group with students assessed the acceptability and practicality of the intervention and study design. Results: The HPS processes were implemented September 2022–September 2023. Students (n = 337), families (n = 49) and staff (n = 22) completed the school audit in November 2022 and November 2023. 237 students completed The Lifestyle and School Questionnaire at baseline (September 2022) and 210 at follow-up (June 2022). Following the initial school audit, the need to improve the school food was identified and became the school focus; results from the second audit reflected a small positive shift in students’ opinion of food provision. It was feasible to capture lifestyle and school culture data using the questionnaire and the same food related priority was captured by the initial questionnaire. However, the timing of the implementation of the changes to the school context meant that this was not captured in the follow up questionnaire results. Conclusion: This study demonstrates that it is possible to administer questionnaires regarding adolescent lifestyle choices in schools. These findings also suggest that it is feasible and acceptable to implement a set of HPS processes. More research is needed to demonstrate an impact on individual health behaviours.